1993
DOI: 10.1002/jmv.1890410308
|View full text |Cite
|
Sign up to set email alerts
|

Partial control of hepatitis delta virus superinfection by immunisation of woodchucks (Marmota monax) with hepatitis delta antigen expressed by a recombinant vaccinia or baculovirus

Abstract: We have successfully limited the level of hepatitis delta viraemia occurring after superinfection of hepadna-virus infected woodchucks by prior immunisation with the short form of the hepatitis delta virus antigen expressed by a recombinant baculovirus or vaccinia virus. This phenomenon occurred in the absence of detectable circulating antibody to hepatitis delta virus antigen and in the absence of evidence of priming of the humoral immune response and may reflect the induction of a cytotoxic T-cell response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Most likely, the alteration of the course of infection by some vaccines (1,10,12,15,16) is due to the ability to elicit appropriate cell-mediated immune responses. However, no correlation has been observed between vaccine efficacy and anti-HD T-cell proliferative responses (12).…”
Section: Vol 80 2006 Hdv Genetic Changes During Acute or Chronic Inmentioning
confidence: 99%
“…Most likely, the alteration of the course of infection by some vaccines (1,10,12,15,16) is due to the ability to elicit appropriate cell-mediated immune responses. However, no correlation has been observed between vaccine efficacy and anti-HD T-cell proliferative responses (12).…”
Section: Vol 80 2006 Hdv Genetic Changes During Acute or Chronic Inmentioning
confidence: 99%
“…It also has been suggested that cytotoxic-T-cell epitopes of HDV may be located at the carboxyl end (amino acids 77 to 195) of S-HDAg (14). In a longitudinal analysis of the HDV genome at different time points during chronic HDV infection, the emergence of amino acid changes at the carboxyl end of S-HDAg (amino acids 170 to 195) usually occurred after a severe hepatitis attack (29).…”
mentioning
confidence: 99%
“…Since the 1980s, several vaccine strategies have been investigated in woodchucks (reviewed in reference 10). Only after immunization with vaccines that are known to induce a CD8 ϩ T cell response, namely, vaccinia virus and DNA-based vaccines, was a modulation of the course of superinfection described (15,24). However, none of the animals had been protected against HDV infection so far.…”
Section: Discussionmentioning
confidence: 99%
“…For the protection of chronically HBV-or WHV-infected patients or woodchucks from HDV superinfection virus-specific T cells would have to circulate in high numbers at the time point of HDV superinfection to inhibit rapid infection of numerous hepatocytes. This could explain why only a delay of the appearance of HDV RNA and not long-term protection was observed after immunization with DNA or vaccinia virus (15,24). Another explanation for the different outcomes of vaccination prior to superinfection or to simultaneous infection may be a dysfunction of HDV-specific T cells in the state of chronic HBV infection by the presence of regulatory T cells (Treg cells).…”
Section: Discussionmentioning
confidence: 99%